Perception and Attitude of Nursing Professionals towards Parental Needs of Hospitalized Children in Pediatric Areas of a Selected Hospital, Vadodara - E.V. , Nirmal Raj; Patel, Ami; P. Joseph, Rajesh; Belagavi, Dayanand (International Journal of Psychosocial Rehabilitation, 2020)
Background: Parental need is an important part of pediatric care right from admission to release of the child. There is often confusion in the awareness and attitude of nursing professionals towards parental needs of children. The individual mores of the pediatric care unit help to build and strengthen the framework of parental needs with satisfaction, communication, information, and relationships between health care workers and parents.Aim: Parental needs are not always met in health care settings during hospitalization. Hence the investigator aimed to assess the perception and attitude of nursing professionals towards parental needs during hospitalization.Material and methods: A quantitative, descriptive study was conducted among 50 nursing professionals of various pediatric hospitals. The samples that met the inclusion and exclusion sampling criteria were recruited by purposive sampling technique. The data on the perception and attitude of the respondents was collected by Likert scale and checklist. Reliability of the tool was done by Cronbach’s alpha and the Spearman prophecy formula. The collected data was categorized further for better understanding. For perception, the investigator assessed the respondents under good and bad perception, and for attitude, samples were categorized as having positive and negative attitudes. The collected data was analyzed by descriptive and inferential statistics.Results: The results discovered that there is no significant association between perception and attitude with their selected socio-demographic characteristics. It was found that the nursing professionals (50) were having good perception and a positive attitude towards parental needs of hospitalized children. There was a positive correlation between the perception and attitude of nursing professionals towards the parental needs of hospitalized children.Conclusion: The study results could sensitize the health care providers and other allied professionals to understand the parental needs of hospitalized children. Repeated assessments have to be conducted in the healthcare settings to promote the relationship between parents and the caregivers.